2017
DOI: 10.1002/pola.28932
|View full text |Cite
|
Sign up to set email alerts
|

Controlled random copolymerization of rac‐lactide and ɛ‐caprolactone by well‐designed phenoxyimine Al complexes

Abstract: The random copolymers poly(LA-ran-CL) have improved properties of degradability, mechanical strength, elasticity, and permeability over the PLA and PCL homopolymers. However, the synthesis of such copolymers is still a great challenge in polymer chemistry. In this contribution, we develop a simple but well-designed phenoxyimine Al complex (4) with bulky Ph 2 CH groups, which achieves controlled random copolymerization of rac-LA and E-CL in a living manner (Ð 5 1.06-1.09). The reactivity ratios of rac-LA and E-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 67 publications
(42 reference statements)
2
31
0
Order By: Relevance
“…Moreover, Ma and Kan exhibited that the rigid backbone in the salen ligand could create a crowded environment around the metal center which reduces the rate of LA and affords the random CL/LA copolymerization . Recently, Li and coworkers have shown that, in a phenoxy‐imine aluminum catalyst system, the increase of steric hindrance around the aluminum center could lead to a strict random copolymer …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Ma and Kan exhibited that the rigid backbone in the salen ligand could create a crowded environment around the metal center which reduces the rate of LA and affords the random CL/LA copolymerization . Recently, Li and coworkers have shown that, in a phenoxy‐imine aluminum catalyst system, the increase of steric hindrance around the aluminum center could lead to a strict random copolymer …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Therefore, the development of the efficient catalysts is a significantly challenging goal to meet the requirements of various applications. Several metal catalyst systems have been reported for the copolymerization of ε-CL and LA ranging from the traditional stannous octoate, 6 to main group catalysts, [11][12][13] transition metal catalysts, [14][15][16][17][18][19] and rare-earth catalysts [20][21][22] leading to varying degree of monomer distribution. In most reports, the truly random copolymer poly(LAran-CL), in which the average sequence lengths of caproyl unit (L CL ) and lactidyl unit (L LA ) equal to 2, 12,23,24 have been very challenging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…LA is typically incorporated first, although CL gives faster rates than LA in homopolymerization reactions. [21][22][23][24][25][27][28][29][31][32][33][34][35][36][37] Aluminum-based catalysts are most efficient for the statistical and controlled ROcP of LA and CL, 35,[38][39][40] thought less toxic catalysts based on zinc 41 and molybdenum 42 have also been successfully employed for this purpose.Organic catalysis for polymerization is a fast developing field in polymer chemistry, offering a number of advantages over metal-catalysis, such as more sustainable processes, reduced toxicity and cost, and easier catalyst synthesis, purification, handling andstorage. 43,44 In this regard, the organocatalyzed ring-opening polymerization (OROP) of LA and CL has been particularly…”
mentioning
confidence: 99%
“…Over the past few years, aluminum complexes coordinated with different types of ligands were designed and prepared, to obtain highly efficient precatalyst for ROP of cyclic esters and produce (co)polyesters with structural diversity. [48][49][50][51][52][53][54] Among the various Al complexes, aluminum-salen complexes bearing salicylaldiminato moiety were found to be a versatile type of catalysts for ROP of both small ring-sized lactones and macrolactone. 9,[55][56][57][58][59] Meanwhile, this type of catalyst showed a certain of stereocontrol ability in the ROP of racemic LA (rac-LA), producing semicrystalline PLA from a mixture of L-LA and D-LA.…”
mentioning
confidence: 99%